Enantiocontrol in Radical Coupling Reactions: A Catalytic [1,2]-Rearrangement of Allylic Ammonium Ylides - Hartley, Will; Kasten, Kevin; Smith, Andrew D. (Synlett, 2025)
The [1,2]-rearrangement of ammonium ylides is a fascinating reaction that has captivated the mechanistically inclined for almost a century. Allylic migration of these ylides is dominated by a thermally allowed concerted [2,3]-rearrangement, with the [1,2]-process usually absent or a minor pathway. As such, development of a [1,2]-selective reaction within allylic systems is an uphill battle. Decades of mechanistic insights have not settled the debate on the true pathway for [1,2]-rearrangement, with a C–N homolysis step followed by a radical coupling within a solvent cage commonly accepted. Herein, we describe our journey through the development of such a process and opine on the broader context in which this chemistry may currently rest.
Keywords: Radical coupling; Rearrangement; Enantioselective organocatalysis; Ylide; Solvent cage; Recombination; Ammonium ylide